Role of fertilizer policy in transforming agriculture of Myanmar - Lwin, Hnin Yu; Myint, Theingi; Than, Shwemar; Aung, Nay Myo; San, Cho Cho; Htut, Tin (International Food Policy Research Institute, 2014)
Approximately 70 percent of the population of Myanmar lives in rural areas and 60 percent of the workforce is involved in agriculture. It is estimated that agriculture contributes to 36 percent of the GDP and 20 percent of the foreign exchange earnings for Myanmar. While agriculture is important for growth in Myanmar, it is primarily rain-fed so agricultural growth is erratic. Due to small farm sizes, increasing food production is dependent on improved policies and technologies that can increase output per hectare. One of the main policy objectives of the Government of Myanmar is to increase food security and the quantity, quality, and variety of crops through partnerships and private sector investment. Improving the private sector participation in the trade and distribution of fertilizer has the potential to reduce fertilizer costs and increase their usage and thus improving farm productivity and food security.